Two Wood-Framed Stock-Anchors from Karaburun, on the Black Sea, Türkiye - Kocabaş, Ufuk (The international journal of nautical archaeology, 2025)
The subject of this article are two wooden frames of stock-anchors discovered by fishermen in 2011 off the coast of Karaburun, Istanbul, in the Black Sea. Documentation has revealed that the remains consist of four pieces belonging to two distinct wooden frames. Carbon-14 analysis dates the anchors to between 580–460 BC. The preserved length of Karaburun Anchor 1 (KA1) is 460.5 cm, with an arm span extending to 184.5 cm. Karaburun Anchor 2 (KA2), with fewer preserved parts, is estimated, based on reconstruction, to have a length of approximately 502 cm. Both anchors primarily used mortise and tenon joints for their connections. It is believed that each may have had a stone stock weighing between 200–240 kg.